How creative destruction functions in corporate entrepreneurial process: An empirical investigation of Schumpeterian concept in engineering firm settings in Pakistan - Muhammad Zubair Alam; Shazia Kousar; Muhammad Rizwan Ullah; Amber Pervaiz (Journal of Innovation and Entrepreneurship, 2022)
Schumpeter's idea of creative destruction (CD) explains innovation functions in organisations. This paper investigates the CD concept in engineering firms by explaining how technical opportunity (TO) transforms into corporate entrepreneurship (CE) actions once opportunities have a market orientation (MO). A survey was conducted using a structured questionnaire with 132 managers of engineering firms in Pakistan. Structural Equation Modelling (SEM) using Partial Least Square (PLS) approach has been used to analyse the data. Results reveal that MO and TO exerts a positive influence on CE. MO is the reason for the emergence of TO, which corporate entrepreneurs in engineering firms exploit. CD intensifies the impact of MO on TO significantly. Opportunity recognition in engineering firms is distinguished and bounded by MO and technical viability. Engineering firms need to identify gaps in the market through naturally occurring obsolescence of products and services (CD) to create TO with appropriate MO. This study has revived a classical debate over opportunity recognition by incorporating external factors to propose the CE model. The Schumpeterian opportunity recognition process and CD have been examined for engineering firms.
Keywords: 650; Corporate entrepreneurship; Creative destruction; Market orientation; Schumpeter's entrepreneur; Technical opportunity recognition